2017
DOI: 10.1186/s12916-017-0836-2
|View full text |Cite
|
Sign up to set email alerts
|

S100β as a serum marker in endocrine resistant breast cancer

Abstract: BackgroundEndocrine therapy is standard treatment for estrogen receptor (ER)-positive breast cancer. However, its efficacy is limited by intrinsic and acquired resistance. Here the potential of S100β as a biomarker and inhibition of its signaling network as a therapeutic strategy in endocrine treated patients was investigated.MethodsThe expression of S100β in tissue and serum was assessed by immunohistochemistry and an enzyme-linked immunosorbent assay, respectively. The S100β signaling network was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…S100B expression was associated with a good overall survival rate in patients with ER-negative breast cancer, and a good DMFS in breast cancer patients as a whole. However, current endocrine therapy-treated patients with a high S100B expression and ER-positive breast cancer reveals poor disease-free survival (18). Based on these findings, it is suggested that ER signaling pathways may affect S100B expression and function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S100B expression was associated with a good overall survival rate in patients with ER-negative breast cancer, and a good DMFS in breast cancer patients as a whole. However, current endocrine therapy-treated patients with a high S100B expression and ER-positive breast cancer reveals poor disease-free survival (18). Based on these findings, it is suggested that ER signaling pathways may affect S100B expression and function.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, a recent study revealed that the serum levels of S100B were an independent prognostic determinant for patients with brain metastasis (17). In the serum of breast cancer patients subjected to endocrine therapy treatment, elevated levels of S100B are associated with a poor disease-free survival (18). Currently, the role of S100B in breast cancer is not well known and the association between the cell metastatic capacity and S100B has not yet been determined.…”
Section: Introductionmentioning
confidence: 96%
“…[33][34][35] Recent studies have also shown that S100 Calcium Binding Protein B (S100B) is upregulated in BC, melanoma, ovarian cancer, and colon adenocarcinoma. [36][37][38][39] Moreover S100B has shown potential as monitoring indicator for ER-positive BC, helping on the assessment of patients regarding to response to endocrine therapy. 36 Midkine (MDK) is an heparin-binding growth factor that is upregulated in various human malignancies and plays an important role in promoting growth, survival, and migration of cancer cells, as well as cancer angiogenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…An LY2 luciferase cell line xenograft and patient breast cancer brain metastatic tumors (T347x and T638x) were expanded in NOD-SCID mice. The primary tumors were resected, grown on gelatin sponges (Spongostan, Johnson and Johnson) as previously described (42) and treated with estrogen combined with vehicle, 4-hydroxytamoxifen (4-OHT), RG108 and a combination of 4-OHT and RG108 for 72 hours. Following treatment, tumor pieces were formalin fixed and paraffin embedded for IHC analysis.…”
Section: Explant Studiesmentioning
confidence: 99%